Knowledge Management System Implementation Readiness Measurement In Knowledge Management Enablers Of Culture, Process, And Information Technology At Pdii - Gilang Ramadhan; Luciana Andrawina; Nia Ambarsari (eProceedings of Engineering, 2015)
Abstract Organization readiness measurement is a very important step to be performed by Pusat Dokumentasi Informasi Ilmiah (PDII) before implementing Knowledge Management System (KM) system. The measurement is intended to help PDII in analyzing its capability to have effective knowledge sharing before PDII implementing KM system. Readiness measurement is done by lowering KM enablers into several dimensions. Dimensions are derived into indicators which serve as questionnaire statements that will be distributed to PDII employees. Readiness scale is using Aydin-Tasci readiness scale. Beside readiness measurement, priority weighting calculation using Analytical Hierarchy Process (AHP) is also done to see which KM enablers and dimensions have to be prioritized by PDII in implementing KM system. Generally, PDII has readiness score of 3.02 (more ready to implement KM system). The results of readiness measurement and priority weight are: Culture readiness score is 3.091 (more ready to implement KM system) with priority weight by 24%, Process readiness score is 2.617 (more ready to implement KM system) with priority weight by 43.6%, and Information Technology readiness score is 3.448 (ready with a few improvements to implement KM system) with priority weight by 32.4%. Keywords: readiness score, priority weight, KM system implementation, KM enablers, dimensions, KM activities